Placement of fin type dental implant in three different surgical situations of alveolar bone - Coen Pramono D (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Three different dental implant placements according to surgical implant bed situations were observed in its bone integration 3 months after dental implant insertion. This observation was done on implant system which has plateau or fin system. Elf implants were placed in the upper jaw in two patients. In case one, two implants were inserted immediately after tooth extraction, and the other six implants were placed in the alveolar crest regions in delayed implantation or in which the teeth had been extracted over 6 months of period. In case two, three implants were inserted in the post trauma region in the anterior maxilla, which the labial plate had been lost and reconstructed with bone grafting procedure using a mixture of alloplastic and autogenous bones. The alveolar reconstruction was needed to be performed due to only thin alveolar crest width was left intact. All of those implants observed showed in good integration.